Empowering Girls Triggers Their Brothers to Compete : Evidence from a Lab-in-the-Field Experiment in Uganda - Buehren, Niklas; Goldstein, Markus; Leonard, Kenneth; Montalvao, Joao; Vasilaky, Kathryn (World Bank, Washington, DC, 2016)
This brief has key messages through an experiment in Uganda, we find that empowering adolescent girls triggers a surge in their brothers’ competitiveness.Understanding preferences for competition is important because competitiveness is a predictor of labor market outcomes. To examine gender differences in preference for competition, the World Bank’s Africa GenderInnovation Lab, in collaboration with researchers from the University of Maryland and ColumbiaUniversity, launched a lab-in-the-field experiment within a randomized control trial of BRAC’scommunity-based Empowerment and Livelihood for Adolescents (ELA) program in Uganda.The ELA program simultaneously provided vocational and life skills training for girls aged 14 to 20. An impact evaluation of ELA showed that it empowered girls along economic and social dimensions: the program increased girls’ participation in self employment, improved girls’ control over their bodies, and shifted deep rooted gender norms held by adolescent girls in communities that participated in the program. Four years after the implementation began, we used a lab-in-the-field experiment to compare communities that received ELA with those that did not. The aim of this experiment was to test whether girl’s empowerment would have a direct impact on girls’ or boys’ competitiveness. To measure preferences for competition, we implemented the experimental protocol of Niederle and Vesterlund (2007). More specifically, participants were asked to select a compensation scheme before performing a simple task, from which we identified their taste to compete. They either chose to be paid according to a competitive tournament scheme or a non competitive piece-rate scheme. The experiment was designed to control for a host of factors such as individual differences in ability, overconfidence, risk aversion, and altruism. Our findings highlight the impact of gender equality on gender differences in competitiveness: when boys are faced with more empowered sisters, they increase their competitiveness. This suggests that the benefits of adolescent girls’ empowerment programs may spill over beyond the participating girls themselves to their brothers. More work needs to be done to understand if the changed behavior in brothers will have persistent effects on girls in the future.